Kajian korpus leksis bahasa Cina berkaitan dengan pendidikan di Malaysia dan China / Lau Su Kia - Lau, Su Kia (2019)
This research was conducted to study the education-related Chinese lexical items in Malaysia and collocations based on the computerized corpus. The corpus data was collected from Malaysian Chinese newspapers, namely Sin Chew Daily, Nanyang Siang Pau and Guang Ming Daily, from January 2011 to December 2013. The texts, which are corpus data comprise the national news and articles discussing education issues in Malaysia. The Malaysian Education Corpus (MEC) formed by the researcher was used as the main corpus of this study, while the China Education Corpus (CEC) as well as the Beijing Language and Culture University Chinese Corpus (BCC) were used to compare with the MEC. The size of BCC is larger than the MEC and CEC. AntConc3.2.4w is the software used in this study. In achieving the first research objective, the education-related Chinese lexical items were extracted from the word list of Antconc and identified. The Dictionary entitled Education Encyclopedia and six scholars who are expert in the field were referred to in the identification process. A total of 593 education-related lexical items were used in MEC. 82 of these lexical items have local features, which are (i) only available in the MEC, and (ii) carry local meanings in MEC if compared to the CEC and BCC. Most of these lexical items refer to schools and students in Malaysia. In attaining the second research objective, 25 high-frequency lexical items related to education were chosen as node words, and the collocation of these node words was examined. The collocates collocated with the node words are derived from the lines of concordance and column of “collocate” in AntConc3.2.4w. The Chinese language collocation pattern proposed by Zhang and Lin (1992) was also used as a framework for this study. Besides, Mutual Information (MI) score was used to assist with the extraction of collocation. The extracted collocations were searched one by one in the comparison corpora. The meaning of each extracted collocation was also done in the same way. Its purpose is to identify local collocations, namely: (i) collocations available only in MEC, and (ii) collocations found in all three corpora, but carry different meanings when used in the MEC. The findings show that the collocation of the “letter word + noun” and “abbreviation of other language + Chinese noun” found in the MEC has not been discussed by Zhang and Lin (1992). The factors that produced such local lexical items and collocations have been discussed and responses from seven informants were referred to in this study. Abbreviation, borrowing, translation from the Malay language and English, endowing local meaning, the difference in meaning and influence of the Chinese dialect are the linguistic factors resulting in the emergence of local lexical items and collocations. This study also further investigated the figurative meanings and emotive meanings (whether positive, negative or neutral) produced by 71 collocations. The data analysis was grounded on the Relevant Theory of Sperber and Wilson (1995). The collocations of the node huájiào (Chinese education) produce various types of figurative meanings. The number of collocations carrying positive emotive meanings is higher than collocations carrying negative and neutral emotive meanings. It is hoped that local lexical items and collocations will be incorporated into the global Chinese dictionaries and collocation dictionaries in the future to make these dictionaries more up-to-date and complete.